INTERIOR OF BEDROOM FROM ANCIENT TO MODERN ERA - Rekhade, Nanadini (International Journal of Research -GRANTHAALAYAH, 2014)
Bedrooms are the primary place of relaxation, where we all retire to take a good sleep and refresh, away from the world and worries. The bedroom interior design is extremely important in order to provide that instant feel of relaxation and here are a few tips: the first thing that meets the eyes are the colors used on the walls, carpets and bed set so, they all must be soothing in pastel colors in order to provide a relaxing effect.